2021
DOI: 10.3390/ma14185288
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Properties of Laser Cladding WC/Ni-Based Composite Layer on Al–Si Alloy

Abstract: The microstructural and wear properties of laser-cladding WC/Ni-based layer on Al–Si alloy were investigated by scanning electron microscope (SEM), X-ray diffraction (XRD), energy dispersive spectrometer (EDS) and wear-testing. The results show that, compared with the original specimen, the microhardness and wear resistance of the cladding layer on an Al–Si alloy were remarkably improved, wherein the microhardness of the layer achieved 1100 HV and the average friction coefficient of the layer was barely 0.14. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the one hand, due to the influence of the convection effect, the WC particles and CoCrFeNi HEA powder melt to each other uniformly in the high-temperature molten pool. On the other hand, the density of WC particles is much higher than that of CoCrFeNi HEA powder, so most WC particles move to the bottom of the coating under the influence of gravity [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, due to the influence of the convection effect, the WC particles and CoCrFeNi HEA powder melt to each other uniformly in the high-temperature molten pool. On the other hand, the density of WC particles is much higher than that of CoCrFeNi HEA powder, so most WC particles move to the bottom of the coating under the influence of gravity [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [68] applied a self-fluxing nickel-based powder coating to an AlSi7Mg aluminum alloy surface via laser cladding. They found that different microstructures were formed in various regions of the coating.…”
Section: Nickel-based Alloysmentioning
confidence: 99%
“…It was found that the combination of finite element numerical simulation to optimize the process parameters of laser melting and rare earth modulation modification could well improve the cracking of the laser-reinforced layer on the surface of aluminum alloy. Wu et al [23] investigated the organization and wear properties of laser-fused nickel-based composite cladding layers on aluminum alloy surfaces. It was found that the hardness value starts to decrease significantly at the end of the middle of the clad layer.…”
Section: Introductionmentioning
confidence: 99%